Phylogenetic relationships and character evolution in Yucca (Agavoideae, Asparagaceae) - Ayala-Hernández, María M.; Fehlberg, Shannon D.; García-Mendoza, Abisaí J.; Solano, Eloy; García-Sandoval, Ricardo; Samain, Marie-Stéphanie (Phytotaxa, 2025)
The current classification of Yucca (Asparagaceae, Agavoideae) is based on morphological characters, mainly on fruit type, caulescence, leaf margin and inflorescence type. To investigate the evolution of these characters, and their potential taxonomic significance as synapomorphies for some groups within Yucca, a phylogenetic analysis was performed with 44 Yucca and eight outgroup species. Divergence times were estimated to produce a suitable phylogenetic framework for the investigation of morphological character evolution. Maximum likelihood and Bayesian inference analyses showed closer phylogenetic relationship between Hesperoyucca and Hesperaloe than either of these two genera with Yucca. The series previously proposed within the genus were not recovered as monophyletic, but based on fruit type we recovered two main clades which we name here clade Aloifolia and clade Rupicola. The ages of the Yucca stem and crown groups were estimated at 14.34 (95% HPD: 14.64–14.2) and 7.45 (95% HPD: 11.31–3.48) million years, respectively. More recent diversification events occurred in both the species with fleshy and dry fruits. Yucca is monophyletic with two main clades, corresponding to the species with dry fruit (clade Rupicola) and fleshy fruit (clade Aloifolia). Partial geographical concordances were observed in both clades. The dispersal type could be a key character in the diversification of the genus. Leaf margin, caulescence, and inflorescence type are not consistent with phylogenetic relationships.